Identifikasi Miskonsepsi Video Pembelajaran Fisika Siswa Kelas X Berbasis Platform Youtube - Nurcahyono, Mochamad Rizky; Suprapto, Nadi (IPF: Inovasi Pendidikan Fisika, 2023)
The current pandemic period does not only have an impact on public health but also has an impact on the economic conditions, education and social life of the community. Therefore, the central and regional governments issue various policies that are preventive in the fields of economy, education and social life of the community. In world education issued a government policy of "distance learning" or online learning. This policy aims so that teaching and learning activities do not stop and students still get their right to acquire knowledge. Distance learning is currently supported by the YouTube, Zoom, Google Class Room, and WhatsApp applications. Distance learning activities also have advantages and disadvantages. One of the advantages of distance learning is that students can participate in learning activities without space restrictions or can be done anywhere. The drawback is that it can lead to misconceptions, because without face-to-face meetings it can directly lead to different concepts of thought and this is a bigger risk than when face-to-face. In this study, the researcher conducted in-depth identification of class X science learning videos on the Youtube platform using a descriptive qualitative research method, where the results of the study found that out of the 33 learning videos identified, there was 1 learning video which could potentially be a misconception but would not become a big problem because in the learning video there is a detailed explanation. In addition, learning to use audio-visual through the YouTube platform is very interesting for students. Therefore, in this distance learning process, it is necessary to have the role of the teacher as a facilitator, namely making improvements based on the results of identifying the causes of the occurrence of misconceptions in the students themselves.